Drill and Practice Berbasis Video terhadap Efektivitas Belajar Matematika Siswa di Sekolah Dasar Negeri 15 Palembang - Siti Aisyah; Muhammad Najib; B. Nuraulia Rahmanita; Andi Prastowo (AR-RIAYAH : Jurnal Pendidikan Dasar, 2023)
The purpose of this study is to determine the differences in the application of video-based drill and practice learning models to student mathematics learning outcomes in fractional materials. The research method used is an experiment in the form of pre-test and post-test group. The subjects involved were 20 students of State Elementary School 15 Palembang. The data collection technique used is in the form of a multiple-choice test of 20 questions. Tests are conducted before and after the learning process. The Paired Test T-Test sample shows that the signification (2-tailed) of the Pre-Test and Post-Test is 0.000<0.005 of the results stated Ha is accepted with the meaning that there are differences in mathematics learning outcomes in students using a video-based drill and practice learning model in grade IV. So it can be concluded that the video-based drill and practice learning model has significant learning outcomes after and before the application of the learning model.